Modern Pedagogical Innovations and Learning Experiences to Enhance Learner Representations and Engagement - Madhakomala, Madhakomala; Situmorang, Marika; Maulida, Rahmi (Journal of Education, Religious, and Instructions (JoERI), 2025)
This article aims to explore and synthesize modern pedagogical approaches and contextual learning experiences that can enhance student representation and engagement. Combining findings from two articles reviewed through a literature review method involving 20 accredited national and international scientific journals (SINTA 1–2 and internationally reputed), this article highlights five main aspects: (1) the integration of digital technology in learning; (2) the application of constructivist strategies; (3) the transformation of the teacher's role into a facilitator; (4) personalized learning and self-regulated learning (SRL); and (5) project-based and contextual learning experiences. All findings are framed within the context of how these approaches provide space for representation and increase student engagement in the learning process. The study results indicate that pedagogical innovations not only revolutionize teaching methods but also position students as active and reflective subjects in the educational process. Keywords: modern pedagogy, student engagement, representation, learning experiences, PjBL